Treinta años de arqueología medieval en España - Quirós Castillo, Juan Antonio (Archaeopress Publishing Ltd, 2018)
This volume presents, in sixteen papers, recent developments and some of the main topics seen in academic Medieval Archaeology studies in Spain. The papers explore some of the emergent and consolidated topics of the discipline, such as landscapes, cities, rural spaces, bio-archaeological records, archaeology of architectures, agrarian archaeology, post-Roman archaeology, colonial archaeology in the Canary Islands and the archaeology of religious minorities, opening new lines of enquiries and providing new theoretical and methodological approaches.